A rights-based approach to environmental protection: the Zimbabwean experience - Madebwe, Tinashe (Juta Law, 2016)
Stemming from the common law, international law and statute, Zimbabwean law has always recognised the prominent role that environmental rights should play in the environmental regulatory framework. In theory, this was based on recognition of the fact that the provision of such rights, and their full enjoyment by citizens, would allow Zimbabweans the opportunity to live in a clean and healthy environment. In addition, through exercising these rights, citizens could directly enforce environmental laws. In practice, however, it appears that deficiencies in the environmental regulatory framework at the institutional level precluded Zimbabweans from fully exercising or enjoying their environmental rights. It was against this backdrop that Zimbabwe in 2013 enacted a new Constitution which entrenched environmental rights in the Declaration of Rights. This was a welcome development which aligned Zimbabwean law with developments across various other jurisdictions which have accorded environmental rights constitutional importance. Importantly, and in light of the seeming deficiencies in the environmental law regulatory framework at the institutional level, which manifested in Zimbabweans not fully exercising, or enjoying, their environmental rights prior to the inception of the Constitution, this article explores whether the inclusion of environmental rights in Zimbabwe's Constitution has been accompanied by sufficient efforts to put in place institutional measures to ensure that citizens exercise and enjoy their rights.